First archaeometric study on medieval glass found in Beja (Southern Portugal). Issue 2 (2nd July 2016) - Coutinho, Inês; Medici, Teresa; Coentro, Susana; Alves, Luís C.; Vilarigues, Márcia
ABSTRACT: During an archaeological intervention that took place in Beja (southern Portugal), at Avenida Miguel Fernandes, between August 2003 and March 2004, a set of 137 silos was discovered. The excavation yielded an assemblage of glass that can be dated between the fourteenth and the seventeenth centuries. For this investigation only the fragments from the medieval contexts were considered in order to provide an overview of the use of glass vessels in a Portuguese town in the fourteenth and fifteenth centuries. A group of eleven medieval glass fragments was chemically characterised by means of µ-PIXE (particle-induced X-ray emission) and UV-vis reflectance spectroscopy. Analysis by µ-PIXE enabled the determination of the chemical composition, and UV-vis reflectance spectroscopy was used as a complementary technique to identify the metallic elements responsible for different colours observed in the glasses. Results showed that the analysed objects are in the majority made of a soda-lime silica glass, indicating a connection with the Mediterranean tradition. Cobalt and copper were the colorants used to obtain the blue and turquoise glasses, respectively, whereas iron is responsible for the green and yellow colours.